Expressão de miostatina e folistatina em ratos castrados submetidos a exercício - Marine, Diego Adorna (2012)
Myostatin (MSTN) is a negative regulator of skeletal muscle growth, while androgens are strong positive regulators of muscle growth and strength. Follistatin (FS) is a nonrelated protein which inhibits MSTN action. The mechanisms of androgens actions are not fully elucidated and evidences suggest that MSTN and testosterone muscle actions may be associated. The objective of this study was to evaluate the influence of exercise training in the expression of MSTN and FS of orquidectomized rats submitted to exercise. Adult male Wistar rats were housed under controlled conditions (20-220 C, 12h light-dark cycle) and were allowed free access to standard rodent chow. After 3 days of acclimation, rats were orchidectomized (O) or shamoperated (S). One group of animals was maintained intact (I). After 1 week, animals were randomly assigned to a training group (O-Train, S-Train and I-Train) or a sedentary group (O-Sed, S-Sed and I-Sed). An 8-week resistance-training period, during which the animals climbed a 1.1-m vertical ladder with weights attached to their tails, was realized. The sessions were performed three times a week, with 4-9 climbs and 8-12 dynamic movements per climb, that were increased the wheight for each climb, and new maximum weight was obtained for new session.The training lasted eight weeks. After this period, rats were decapitated. White gastrocnemius muscle were dissected, immediately frozen in liquid nitrogen and stored at -700 C for subsequent analysis. MSTN and FS mRNA was quantified by real time RT-PCR. The animals were maintained according to the local University Committee guidelines for the care and use of laboratory animals. P < 0.05 was considered statistically significant. MSTN mRNA expression was significantly higher in gastrocnemius muscle of O-Sed group than in I-Sed group. FS mRNA expression was significantly lower in S-Train and O-Train groups than in I-Sed and I-Train groups. The results indicate that MSTN expression increases in skeletal muscle of orchidectomized rats and is not influenced by resistance training. FS mRNA can to be influenced for resistance training and other hormones or proteins.